2018
DOI: 10.2337/dc18-0548
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic Variation and Cardiovascular Risk in the Veterans Affairs Diabetes Trial

Abstract: Our analysis indicates that in the VADT, variability of fasting glucose plays a role in the development of CVD complications beyond the influence of standard fasting glucose measures. The adverse consequences of fasting glucose variability on CVD appear greatest in those receiving intensive glucose control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
93
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(98 citation statements)
references
References 38 publications
5
93
0
Order By: Relevance
“…[30][31][32] The association of HbA1c variability with all-cause mortality in this study is consistent with most previous results 7,18,21,[26][27][28][29] ; however, one study did not find such an association. 25 The mechanism underlying this association remains unclear. High glycaemic variability is associated with a high risk of severe hypoglycaemia.…”
Section: T a B L E 1 Baseline Characteristics Of The Study Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…[30][31][32] The association of HbA1c variability with all-cause mortality in this study is consistent with most previous results 7,18,21,[26][27][28][29] ; however, one study did not find such an association. 25 The mechanism underlying this association remains unclear. High glycaemic variability is associated with a high risk of severe hypoglycaemia.…”
Section: T a B L E 1 Baseline Characteristics Of The Study Subjectsmentioning
confidence: 99%
“…Beck et al proposed that estimation of glycaemic control using HbA1c alone may not be accurate for some patients . Recently, the relationships of HbA1c variability with diabetic complications and mortality in patients with T2D have piqued research interest. A recent study reported that the association of mean HbA1c with all‐cause mortality disappeared after adjustments for HbA1c variability measures, suggesting that HbA1c minimally influences all‐cause mortality.…”
Section: Introductionmentioning
confidence: 99%
“…For example variability in heart rate or blood pressure has been linked to CHF 7 and all‐cause mortality 7 . In addition, variability in blood glucose or cholesterol has been related to CHD, 8 AF 9 and all‐cause mortality 10 . While liver enzymes can also fluctuate during the course of life, to date, no study has investigated whether liver enzyme variability is a predictor of heart disease and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Excess variability in glucose and HbA 1c levels that results from chronic fluctuations over time may indicate increased cardiovascular risk in the diabetic population, 11,12 although the possibility has been controversial. [12][13][14][15] Patients with established coronary artery disease (CAD) may be particularly susceptible to poor glucose control. The few studies of longitudinal HbA 1c variation in patients with diabetes and CAD have assessed a limited number of HbA 1c measures, had short follow-up, or were based on heterogeneous populations.…”
Section: Introductionmentioning
confidence: 99%